2015
DOI: 10.1016/j.jcp.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Coupling a local adaptive grid refinement technique with an interface sharpening scheme for the simulation of two-phase flow and free-surface flows using VOF methodology

Abstract: Citation: Malgarinos, I., Nikolopoulos, N. and Gavaises, M. (2015). Coupling a local adaptive grid refinement technique with an interface sharpening scheme for the simulation of two-phase flow and free-surface flows using VOF methodology. Journal of Computational Physics, 300, pp. 732-753. doi: 10.1016/j.jcp.2015.08.004 This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent AbstractThis study presents the implementation of an interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…The model has been successfully validated in [33,54,63,67,68] for cases including the motion of a free falling droplet, droplet breakup, droplet evaporation and droplet impact onto a solid substrate.…”
Section: Numerical Model and Methodologymentioning
confidence: 99%
“…The model has been successfully validated in [33,54,63,67,68] for cases including the motion of a free falling droplet, droplet breakup, droplet evaporation and droplet impact onto a solid substrate.…”
Section: Numerical Model and Methodologymentioning
confidence: 99%
“…The CFD model has been validated and used for many applications including the aerodynamic breakup of droplets with high density ratios as described in [17][18][19][20]. The simulations are performed in a 2-D axisymmetric domain with the commercial CFD tool ANSYS FLUENT v16 [21], along with various user defined functions (UDFs) for the implementation of the adaptive local grid refinement [22] and the adaptive time-step for the implicit VOF solver. With the current grid resolution employed, drop radius is resolved by 192 cells per Radius (cpR) with minimum cell size ranging from 0.48μm up to 6.25μm depending on the droplet radius; systematic runs with 48, 96, 192 and 384cpR have revealed that the resolution of 192cpR is adequate for achieving a grid independent solution.…”
Section: Numerical Model and Computational Setupmentioning
confidence: 99%
“…The computational cells are squares at the bubble region (1.5 R0) and quadrilateral at the rest of the domain; this is shown in Figure 1. To enhance the accuracy of computations and achieve a low computational cost, an adaptive local grid refinement technique [19] is used. The grid resolution expressed as cells per Radius (cpR) range between 400 cpR for the maximum bubble radius and 8cpR for the minimum one.…”
Section: Mathematical Modelsmentioning
confidence: 99%
“…Far from the bubble, boundary conditions of constant pressure and temperature are applied, while only the half of the bubble is simulated by using symmetry boundary condition. The CFD simulations are performed with the commercial CFD tool ANSYS FLUENT v16 [20], along with various user defined functions (UDFs) for the implementation of the adaptive local grid refinement method in Malgarinos et al [19] and the adaptive time-step for the implicit VOF solver.…”
Section: Mathematical Modelsmentioning
confidence: 99%